THE SUPPORTING ASPECTS OF POLITICAL FEMINISM OF THE CROWN SERIES - Rd. Ananda Iqbaldi; Tri Wahyu Retno Ningsih (Jurusan Sastra Indonesia, 2021)
Feminism is the struggle of women to fight for their voice to be heard is a never-ending struggle that can be seen on media even in literature. Women ask for the equality as men received naturally, even in literature women depicted as someone hysterical and vulnerable however in the late 20th century until today the depiction of strong women is getting common even in Political world. The aspects of Political Feminism in The Crown series is the object of the study in order to uncover the aspects within the ideology itself. There are 30 data within the series that consists of Political Feminism with aspects of Political, Liberal, binary aspect of Political and Liberal. Within political feminism there are aspects that can be found and not political aspect only but also others such as liberal, etc.